Functional Genes and Bacterial Communities During Organohalide Respiration of Chloroethenes in Microcosms of Multi-Contaminated Groundwater - Hermon, Louis; Hellal, Jennifer; Denonfoux, Jérémie; Vuilleumier, Stéphane; Imfeld, Gwenaël; Urien, Charlotte; Ferreira, Stéphanie; Joulian, Catherine (Frontiers in Microbiology, 2019)
Microcosm experiments with CE-contaminated groundwater from a former industrial site were set-up to evaluate the relationships between biological CE dissipation, dehalogenase genes abundance and bacterial genera diversity. Impact of high concentrations of PCE on organohalide respiration was also evaluated. Complete or partial dechlorination of PCE, TCE, cis-DCE and VC was observed independently of the addition of a reducing agent (Na2S) or an electron donor (acetate). The addition of either 10 or 100 μM PCE had no effect on organohalide respiration. qPCR analysis of reductive dehalogenases genes (pceA, tceA, vcrA, and bvcA) indicated that the version of pceA gene found in the genus Dehalococcoides [hereafter named pceA(Dhc)] and vcrA gene increased in abundance by one order of magnitude during the first 10 days of incubation. The version of the pceA gene found, among others, in the genus Dehalobacter, Sulfurospirillum, Desulfuromonas, and Geobacter [hereafter named pceA(Dhb)] and bvcA gene showed very low abundance. The tceA gene was not detected throughout the experiment. The proportion of pceA(Dhc) or vcrA genes relative to the universal 16S ribosomal RNA (16S rRNA) gene increased by up to 6-fold upon completion of cis-DCE dissipation. Sequencing of 16S rRNA amplicons indicated that the abundance of Operational Taxonomic Units (OTUs) affiliated to dehalogenating genera Dehalococcoides, Sulfurospirillum, and Geobacter represented more than 20% sequence abundance in the microcosms. Among organohalide respiration associated genera, only abundance of Dehalococcoides spp. increased up to fourfold upon complete dissipation of PCE and cis-DCE, suggesting a major implication of Dehalococcoides in CEs organohalide respiration. The relative abundance of pceA and vcrA genes correlated with the occurrence of Dehalococcoides and with dissipation extent of PCE, cis-DCE and CV. A new type of dehalogenating Dehalococcoides sp. phylotype affiliated to the Pinellas group, and suggested to contain both pceA(Dhc) and vcrA genes, may be involved in organohalide respiration of CEs in groundwater of the study site. Overall, the results demonstrate in situ dechlorination potential of CE in the plume, and suggest that taxonomic and functional biomarkers in laboratory microcosms of contaminated groundwater following pollutant exposure can help predict bioremediation potential at contaminated industrial sites.